Enhancing quality of life through singing : a music therapy study into Huntington's Disease : a research dissertation presented in partial fulfillment of the requirements for the degree of Master of Music Therapy at the New Zealand School of Music, Wellington, New Zealand - Van Beek, Sacha (Massey University, 2012)
This mixed methods study investigated whether the process of singing in music therapy can enhance the quality of life of patients with Huntington’s Disease. It took place in New Zealand, over a two-month period, in a residential home dedicated to the rare condition. The research involved five participants: two residents diagnosed with Huntington’s Disease who participated in individual music therapy sessions, two caregivers at the facility, and the music therapy student (MTS). The study endeavoured to answer the research question by triangulating three data sources. Data sources included; the MTS’s clinical notes of the sessions, semi-structured interviews with the staff members and a short questionnaire developed by the researcher which involved gathering the personal self-rated scores from the resident participants. A thematic analysis was undertaken with the two text-based data sources (clinical notes and interview transcripts) and the questionnaire scores were collated for each case. However the questionnaire results were deemed predominantly invalid. The triangulation of findings found that participants observed the process of singing had contributed to areas of quality of life for both of the residents, by providing them with: 1) a stimulus for socialisation; 2) emotional and psychological support; and 3) support for their remaining cognitive and physical ability. The outcome of the study found that the process of singing stimulated the resident participants in two contrasting ways and their motivation to participate was not only the singing itself but also the music in the session, instrumental play and the relationship between the residents and the MTS. From the perspectives of the participants consulted in this study it was concluded that the results from this research added some rich detail to the current literature available. Findings also concluded that residents, caregivers and the MTS herself valued the process of singing in music therapy and regarded it as an important intervention when seeking to preserve the quality of life of Huntington’s patients.
Keywords: Music therapy; Huntington's chorea patients; Singing; Voice; Therapeutic use